Education Management in Curriculum Development A Study in Madrasah Diniyah Takmiliyah Awaliyah Kesatuan Agam Tuo (MDTA-KAT) - Balqis Nyimas Zhafirah; Khairul Anwar; Izul Mar’ati; Eka Nuraini; Aliya Aliya; Nabila Nabila (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
ENGLISH: Education Management in Curriculum Development at Madrasah Diniyah Takmiliyah AwaliyahObjective: This study aims to describe and empirically analyze the curriculum development management process at Madrasah Diniyah Takmiliyah Awaliyah (MDTA) KAT Curup Talang Rimbo Baru. Method: This study used a qualitative approach, employing in-depth interviews, observations, and documentation. Informants included the madrasah principal, teachers, and foundation administrators. Results: The results showed that MDTA curriculum development refers to the policies of the Ministry of Religious Affairs and is developed autonomously through the Diniyah Takmiliyah Communication Forum (FKDT). The curriculum is developed collaboratively with an emphasis on Islamic values, the ability to read the Qur'an, and character building. Curriculum management is carried out in a participatory manner, with routine evaluations every semester. The main obstacles include limited funding, low government attention, and limited human resources. Conclusion: MDTA curriculum development management has been quite effective despite facing various limitations. Contribution: Reinforces the curriculum management model in non-formal religious education.INDONESIAN: Manajemen Pengembangan Kurikulum di Madrasah Diniyah Takmiliyah AwaliyahTujuan: Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis secara empiris proses manajemen pengembangan kurikulum di Madrasah Diniyah Takmiliyah Awaliyah (MDTA) KAT Curup Talang Rimbo Baru. Metode: Penelitian menggunakan pendekatan kualitatif dengan teknik pengumpulan data melalui wawancara mendalam, observasi, dan dokumentasi. Informan meliputi kepala madrasah, guru, dan pengurus yayasan. Hasil: Hasil penelitian menunjukkan bahwa pengembangan kurikulum MDTA mengacu pada kebijakan Kementerian Agama dan dikembangkan secara otonom melalui Forum Komunikasi Diniyah Takmiliyah (FKDT). Kurikulum disusun secara kolaboratif dengan penekanan pada nilai keislaman, kemampuan membaca Al-Qur’an, dan pembentukan akhlak. Pengelolaan kurikulum dilakukan secara partisipatif dengan evaluasi rutin per semester. Kendala utama meliputi keterbatasan pembiayaan, rendahnya perhatian pemerintah, dan keterbatasan sumber daya manusia. Kesimpulan: Manajemen pengembangan kurikulum MDTA telah berjalan cukup efektif meskipun menghadapi berbagai keterbatasan. Kontribusi: Memberikan penguatan model pengelolaan kurikulum pada pendidikan keagamaan nonformal.